SP0116 Lost in Translation – How to Understand What Clinicians Talk About. (9th June 2015) - Scheel-Toellner, D.
Abstract : For successful translational research it is of key importance that communication between researchers mainly based in the clinic and those working in a laboratory setting functions effectively. This presentation will highlight some characteristic problems the speaker has encountered at the interface of clinical and non-clinical staff and will offer a few suggestions to avoid misunderstandings and misconceptions Disclosure of Interest: None declared